Efecto de la fertilización con calfos, malezas acuáticas y gallinaza en la adaptación de seis especies pioneras para revetalización de zonas erosionadas del municipio de Bojacá, Cundinamarca; parte i:análisis de crecimiento con información primaria - Pedroza Manrique, Jaime; Donado Novoa, William (Revista Científica, 2006)
The use of iron slag, aquatic weeds and hen droppings, at the time of the establishment of Baccharis bogotensis, Dodoena viscosa, Lantana camara, Baccharis latifolia, Myrica parvifolia and Hesperomeles goudotiana, in Bojacá, Cundinamarca, shows, through the growth analysis with primary information that the fertilization with hen droppings is the best treatment in the adaptation of these evaluated species. B. bogotensis was the best adapted species to the zone of study, surpassing, up to four times, to the other species in the biomass and leaf area increases. M. parvifolia showed the lowest biomass and leaf area increases, in the three teatments. H. goudotiana did not respond to the analyzed treatments, this indicating it null adaptation to the conditions of the zone of study.